Is the RFID technology ready to integrate supply chain activities?. (14th January 2008) - Chan, H.K.; Chan, Felix T.S.
Radio Frequency Identification (RFID) is not a new technology and has been introduced for military applications for a long time. Nevertheless, it has been recognised as a device that may soon change the mode of operations throughout the supply chain. There is no question that the technology will reduce labour and improve accuracy in inventory management by improving inventory visibility. However, a review of recent research and the development of RFID technology in supply chain related applications indicated that deployment of the technology are restricted to the mandates of some giant players in the industries. It is still unclear that how return on investment of RFID-based projects could be justified. This paper aims to present a review of the technology and some recent development of RFID in relation to supply chain applications. Future research direction is then suggested.